Pengaruh Sistem Pembelajaran Full Day School Terhadap Perkembangan Peserta Didik - Chieka Aisyah Kinanti; Kailla Putri Aisyah; Sylmi Adila; Alma Miftaqiyah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This research is based on the legalization of the Full Day School (FDS) learning system in July 2017 which has been stipulated in the Kementerian Pendidikan dan Kebudayaan Indonesia Nomor 23 Tahun 2017 tentang Hari Sekolah . Although initially the full day school system was considered to have a positive impact on students, the implementation of full day school also encountered several obstacles which in turn would have a negative impact, one of which was the lack of interaction between students and family members and the lack of socialization of students with the community. the environment where he lives. The research method used to write this article uses a quantitative approach with data collection methods derived from library research to find out in more detail the impact of implementing a full day school system in schools for students.